2009
DOI: 10.3945/jn.109.108902
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to the Mediterranean Diet Is Associated with Lower Abdominal Adiposity in European Men and Women

Abstract: Given the lack of consistent evidence of the relationship between Mediterranean dietary patterns and body fat, we assessed the cross-sectional association between adherence to a modified Mediterranean diet, BMI, and waist circumference (WC). A total of 497,308 individuals (70.7% women) aged 25-70 y from 10 European countries participated in this study. Diet was assessed at baseline using detailed validated country-specific questionnaires, and anthropometrical measurements were collected using standardized proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

21
93
3
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 153 publications
(123 citation statements)
references
References 41 publications
21
93
3
4
Order By: Relevance
“…Computer-assisted modelling of individual diets identified that the most important foods that enable people to fulfil nutritional requirements (except for vitamin D) are those characteristic of the MDP (63) . Surveys have repeatedly shown that adherence to an MDP is also associated with a healthier body weight (64,65) , reduced waist circumference as a marker of central obesity (66) , and lower incidence of the metabolic syndrome (67) and type 2 diabetes (68,69) . The Mediterranean diet may positively influence the ageing process (70) by delaying the evolution of cognitive decline linked to Alzheimer's disease (71) and vascular dementia, which is often documented a long time before the clinical diagnosis of dementia (72) .…”
Section: Development Of the Med Diet 40 Frameworkmentioning
confidence: 99%
“…Computer-assisted modelling of individual diets identified that the most important foods that enable people to fulfil nutritional requirements (except for vitamin D) are those characteristic of the MDP (63) . Surveys have repeatedly shown that adherence to an MDP is also associated with a healthier body weight (64,65) , reduced waist circumference as a marker of central obesity (66) , and lower incidence of the metabolic syndrome (67) and type 2 diabetes (68,69) . The Mediterranean diet may positively influence the ageing process (70) by delaying the evolution of cognitive decline linked to Alzheimer's disease (71) and vascular dementia, which is often documented a long time before the clinical diagnosis of dementia (72) .…”
Section: Development Of the Med Diet 40 Frameworkmentioning
confidence: 99%
“…As compared to individuals on a Mediterranean diet, those consuming a diet high in saturated fat have increased weight gain, a greater volume of visceral adipose tissue, larger waist circumference and more cardiovascular disease mortality. [9][10][11] Evidence suggests that diets high in saturated fat and relatively low in polyunsaturated and monounsaturated fatty acids contribute to the pathogenesis of both mood and metabolic disorders during obesity. A successful reducing diet is one that an individual can adhere to for several months to lose 5% to 10% of initial weight.…”
Section: Discussionmentioning
confidence: 99%
“…Şişmanlığın etiyolojisi multifaktöriyel olmakla birlikte, temel fizyolojik neden, fiziksel aktivitenin olmaması/azlığı ile yüksek enerji alımı arasındaki dengesizliktir. 6,14 Şişmanlık; KVH, kanser, Tip 2 DM gibi çeşitli kronik hastalıklar için önemli bir risk faktörüdür. 3 Akdeniz diyeti, hafif şişmanlık ve şişmanlığın önlenmesi ve düzeltilmesi konularında ilgi görmektedir.…”
Section: Akdeni̇z Di̇yeti̇ Ve şİşmanlikunclassified
“…Yüksek miktarda zeytinyağı, zeytin, meyve ve sebzeler, tahıllar (çoğunlukla tam tahıllı besinler), baklagiller ve yağlı tohumlar; ortayüksek düzeyde balık, orta düzeyde yumurta, kümes hayvanları ve süt ürünleri ile düşük düzeyde kırmızı et ve ürünlerinin tüketimi bu diyetin temel özelliklerindendir. 1,2,5,6 Dinî ve sosyal normlara ters olmadığı sürece, bu diyette şarap tüketimi orta dü-zeyde kabul edilebilmektedir. 1,6 Tek bir Akdeniz diyeti olmadığı vurgulanmalıdır; ancak her ülke-nin kendi kültürüne uygun olarak temel bir içerik etrafında çeşitlilik mevcuttur.…”
unclassified
See 1 more Smart Citation